STUDENTS’ RESPONSE TOWARD THE IMPLEMENTATION OF MINDOMO IN WRITING DESCRIPTIVE TEXT AT THE SEVENTH GRADE THE STUDENTS IN CIMAHI - Novianti, Annisa; Kareviati, Evie (IKIP Siliwangi, 2021)
This study aims to describe students' responses toward the implementation of Mindomo in writing description text at seventh-grade students in Cimahi. This study used descriptive qualitative methods. The participant of the study is 33 students’ junior high school in Cimahi. The result of this study showed that the implementation of Mindomo in teaching writing descriptive text gave positive responses to 81,80%. This positive response was shown with the enthusiasm of students during the learning process. Aspects of attention get the largest average score of around 24.54, which shows students are more interested in the learning process of writing using the Mindomo application. Besides, the aspect of confidence and satisfaction get the lowest score 12, it can be seen that the students are lack of confidence and have a fear of writing.